Travel Needs for Tourism Apps Features for Tourists in Kuching, Sarawak - Aimuni Athirah, Latif (University Malaysia Sarawak, 2023)
Tourism agencies and businesses must now have in-depth knowledge of tourists needs in order to provide places to visit, accommodation, and transportation. The development of useful features that can be used as tools to improve tourism marketing is indeed an important component of the tour operator business. The needs of tourists must be taken into account when developing app features in order to fully satisfy their needs and serve as a model for travel businesses and agencies. The Sarawak government encourages in-depth research because the tourism industry depends on smart technology to draw in more visitors and improve their travel experiences. The majority of tourists use smart technology while travelling, which includes features like location queries, local restaurant reviews, or mobile payments through smartphones. App features are very helpful in growing the tourism sector to boost the economy and give tourists the best possible travel experience. In connection with this, the researcher conducted additional research on travel requirements, the contribution of features of tourism apps to tourists needs, and how these findings will serve as guidelines for businesses and travel agencies. A quantitative method was used to further this research among tourists in the Kuching, Sarawak area. The findings indicate that pleasure, cost, and feasibility of travel include safety and security for tourists visiting Kuching. It has been demonstrated that these features have an effect on travel agencies and tourist needs. The research’s final outcome is a conceptual framework that can be used as a guideline by businesses and tourism organizations to develop apps for their own use. Keywords: Tourism sector, tourism organization, apps, travellers.